Regulation of lifespan in Drosophila by modulation of genes in the TOR signaling pathway. - Kapahi, P.; Zid, B.M.; Harper, T.; Koslover, D.; Sapin, V.; Benzer, S. (Current Biology, 2004)
In many species, reducing nutrient intake without causing malnutrition extends lifespan. Like DR (dietary restriction), modulation of genes in the insulin-signaling pathway, known to alter nutrient sensing, has been shown to extend lifespan in various species. In Drosophila, the target of rapamycin (TOR) and the insulin pathways have emerged as major regulators of growth and size. Hence we examined the role of TOR pathway genes in regulating lifespan by using Drosophila. We show that inhibition of TOR signaling pathway by alteration of the expression of genes in this nutrient-sensing pathway, which is conserved from yeast to human, extends lifespan in a manner that may overlap with known effects of dietary restriction on longevity. In Drosophila, TSC1 and TSC2 (tuberous sclerosis complex genes 1 and 2) act together to inhibit TOR (target of rapamycin), which mediates a signaling pathway that couples amino acid availability to S6 kinase, translation initiation, and growth. We find that overexpression of dTsc1, dTsc2, or dominant-negative forms of dTOR or dS6K all cause lifespan extension. Modulation of expression in the fat is sufficient for the lifespan-extension effects. The lifespan extensions are dependent on nutritional condition, suggesting a possible link between the TOR pathway and dietary restriction.